Economic openness, institution, and environmental degradation in a small open dynamic economy: recent evidence from Malaysia - Chan, Fatt Cheah; Abdul-Rahim, Abdul Samad; Saari, Mohd Yusof; Mohd Naseem, Niaz Ahmad (Springer, 2022)
This paper aims to investigate the impact of the economic openness and institutional quality in explaining the environmental degradation in Malaysia that covers from 1980 to 2019. By using an innovative autoregressive distributed lag (ARDL) technique, the result indicates that economic openness that is measured through the trade and FDI are unequivocally environmental improving. Meanwhile, the institutional reforms also appeared to actualize the beneficial effect of environmental emission. The findings show that economic openness and institutional quality act as a key driving force to further curb the CO2 emission and in turn to reduce the environmental pollution. This suggests that countries with adequate trade, FDI, and institutional settings like Malaysia are on the right track to reinforce all efforts in bringing down pollution. Therefore, environmental quality can be improved through the greater ability and willingness to enforce environmental regulations and higher trade liberalization process, which is usually associated with higher income, more economic development, and better environment.